Structure and Magnetoresistive Properties of Thee-layer Film Systems Based on Permalloy and Copper - Yu.O. Shkurdoda; А.М. Chornous; V.B. Loboda; Yu.М. Shabelnyk; V.О. Kravchenko; L.V. Dekhtyaruk (Журнал нано- та електронної фізики)
Structural and phase composition and magnetoresistive properties of three-layer film systems based on permalloy and copper were investigated. The samples were obtained by layer by layer condensation method with followed heat treatment to the 300-700 K temperature range. Shown that the spin-dependent scattering of electrons realizing in the range of layer thicknesses (dCu = 6-15 nm and dPy = 25-40 nm) of the condensed and annealed at 400 K samples. The Maximum GMR observed after annealing the samples at 400 K and annealing to 550 K leads to anisotropic magnetoresistance occurrence.